Space-time-frequency processing of synthetic aperture radar signals - Barbarossa, S.; Farina, A. (IEEE transactions on aerospace and electronic systems, 1994)
The subject of this work is the detection and high resolution microwave imaging of objects moving on the ground and observed by an airborne radar. The proposed approach is based on a combined space-time and time-frequency processing. The space-time processing makes use of a linear array antenna and exploits the radar motion for filtering the received echoes in order to improve as much as possible the signal-to-disturbance ratio. The signal is then mapped onto the time-frequency domain, by computing its Wigner-Ville distribution, for a further filtering and for estimating its instantaneous frequency, necessary for the formation of a high resolution image of the moving object.< >